34.1.4.2.9 Synthesis by Substitution of Hydroxy Groups in Alcohols (Update 2016) - Vandamme,M.; Paquin,J.-F. (Knowledge Updates 2016/1, 2016)
This chapter is an update to the earlier Science of Synthesis contribution describing methods for the synthesis of fluoroalkanes by substitution of hydroxy groups in alcohols. It focuses on the literature published in the period 2005–2015.
Keywords: Referencework; Science of Synthesis; nucleophilic substitution; fluorodehydroxylation; alcohols; fluoroalkanes; elimination side-reactions; stereoselectivity; chemoselectivity